Short-term and long-term outcomes in patients with cryptococcal meningitis after ventriculoperitoneal shunt placement - Wen, Junxian; Yin, Rui; Chang, Jianbo; Chen, Yihao; Dong, Xiying; Cao, Wei; Ma, Xiaojun; Li, Taisheng; Wei, Junji (Frontiers in Neurology, 2022)
Abstract Objective: The purpose of this study was to assess the short-term, long-term outcomes of ventriculoperitoneal shunt (VPS) placement in cryptococcal meningitis (CM) patients. Method: We performed a retrospective analysis of all patients with CM admitted to Peking Union Medical College Hospital from September 1990 to January 2021. We collected related clinical features to analysis the short and long-term outcomes of VPS at one month and one year at least following therapy, respectively. Overall survival (OS) were compared among patients by the Kaplan-Meier method with log-rank test. Univariable and multivariable analyses were also performed using the Cox proportional hazard model to identify statistically significant prognostic factors. Result: We enrolled 98 patients, fifteen of whom underwent VPS. Those who received VPS had a lower CSF cryptococcus burden (1:1 vs 1:16; P=0.046), lower opening pressures (173.3 mmH20 vs 224 mmH20; P=0.009) at lumbar punctures and a lower incidence of critical cases (6.7% vs 31.3%; P=0.049). According to our long-term follow up, no significant difference shown in the Barthel Index (BI) between the two groups. Two patients in the VPS group suffered postoperative complications and had to go through another revision surgery. According to survival analysis, The Kaplan-Meier plots showed that critical patients with VPS had better survival in OS (p < 0.009). Multivariable analyses for critical patients showed VPS was independent prognostic factors. Conclusion: VPS could reduce the intracranial pressure (ICP), decrease the counts of Cryptococcus neoformans by a faster rate and reduce the number of critical cases. VPS used in critical CM patients has a significant impact on survival, but it showed no improvement in the long-term Barthel Index (BI) versus conservative treatment and could lead to postoperative complications.